2017
DOI: 10.12973/eurasia.2017.01041a
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a DANP with VIKOR Approach for Establishing the Model of E-Learning Service Quality

Abstract: In practical environments, e-learners encounter service providers of varying quality. A wide range of criteria are used to assess service quality, but most of these criteria have interdependent or interactive characteristics, which can make it difficult to effectively analyze and improve service quality. The purpose of this study is to address this issue using a hybrid MCDM (multiple criteria decision-making) approach that includes the DEMATEL (decision-making trial and evaluation laboratory), DANP (the DEMATE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Besides the mentioned works, others present the utilization of different MCDM techniques for e-learning course evaluation and selection. For the resolving of the problem of evaluation of e-course quality, the authors have proposed the application of the proximity indexed value (PIV) model [58], fuzzy ANP [59], DANP and VIKOR [60], and so on. The conducted numerical case study presented in this paper, as well as the comparison with the results of the given authors, confirmed that the proposed approach is also very beneficial for e-learning course evaluation and selection because the obtained results clearly outlined the crucial characteristics and the position of the specific e-learning course comparing to the others.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the mentioned works, others present the utilization of different MCDM techniques for e-learning course evaluation and selection. For the resolving of the problem of evaluation of e-course quality, the authors have proposed the application of the proximity indexed value (PIV) model [58], fuzzy ANP [59], DANP and VIKOR [60], and so on. The conducted numerical case study presented in this paper, as well as the comparison with the results of the given authors, confirmed that the proposed approach is also very beneficial for e-learning course evaluation and selection because the obtained results clearly outlined the crucial characteristics and the position of the specific e-learning course comparing to the others.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of previous attempts in flipped e-learning teaching, the lack of literature is still difficult to identify and analyze the elements and sub-elements of flipped e-learning systems in sustainable science education [23][24][25]. Thus, these operational methods are necessary to adjust sustainable science education of flipped e-learning system with various decision-makers on multiple criteria [26,37,38]. In particular, these operational techniques and methods are barely used in the topic of neither sustainability education nor flipped e-learning systems.…”
Section: Discussionmentioning
confidence: 99%
“…For prioritizing various criteria in science education for sustainable development together with many different disciplines and regulations, the multi-criteria decision analysis (MCDA) method can be applied along with the pairwise comparison method (PCM) and the analytic hierarchy process (AHP) through flipped e-learning system [26][27][28][29]. Here, Jain et al described that multi-criteria decision-makings on multiple components could be used for initiating and ranking flipped e-learning systems of the extensive selection and assessment of flipped e-learning systems [30].…”
Section: Elements' and Sub-elements' Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results are recorded for data analysis using the Analyze Hierarchical Process (AHP) method associated with the VIKOR method (Wibawa et al, 2019), (Dincer & Hacioglu, 2013). These two methods are groups of Multi-Criteria Decision Making (MCDM) and have the same role in both methods, namely for the selection process and evaluation of all processes and activities that indicate ranking (Thipparat & Thaseepetch, 2013), thus both AHP and VIKOR methods can collaborate into a single method that can deal with problems related to the selection process for swimming athletes (Yang et al, 2017)for all swimming styles that are often competed in national and international high-level competitions, especially regarding existing swimming style variants.…”
Section: Introductionmentioning
confidence: 99%